Sensory Test and Molecular Marker Based-Selection for Aromatic Rice in the F3 Progenies - Nono Carsono; Amalia Purdianty; Santika Sari; Citra Bakti (Fakultas Pertanian Universitas Padjadjaran, 2020)
Aromatic rice is a special type of rice that highly preferred by people in Asia due to the presence of aroma. Aroma in rice is determined by 2-acetyl-1-pyrroline (2AP) compound which is controlled by a recessive fgr gene. A hybridization between cv. Sintanur (aromatic rice) and PTB33 (non-aromatic, resistant to brown planthopper/BPH) has been done in order to develop aromatic rice lines that resistant to BPH. In the F2 progeny, molecular marker-based selection and bioassay for the brown planthopper resistant lines have been carried out; however selection for the aromatic trait has not been performed yet. The objective of this study was to obtain the F3 progeny’s individual with aromatic trait. Sensory test was conducted by KOH 1.7% solution, meanwhile molecular markers applied were ESP (External Antisense Primer), IFAP (Internal Fragrant Antisense Primer), INSP (Internal Non fragrant Sense Primer) and EAP (External Antisense Primer). Eighty-eight plants from two selected (SP#31 and SP#224) F3 lines progenies derived from cv. Sintanur and PTB33 have been evaluated in this study. Detection by molecular markers found seventy-five genotypes (85.23%) were homozygous recessive (aromatic rice) and one was heterozygous (non-aromatic). Eighty-five (96.59%) genotypes were aromatic as detected by sensory test alone. Seventy-two (81.82%) genotypes were categorized as aromatic rice based on sensory test and molecular markers. Due to inconsistency results from each method alone, it is advised both methods to be applied to ensure the reliability and the accuracy since aroma in rice is affected by genetic composition and environment conditions. Selected genotypes will be continued for breeding program in developing aromatic rice with improved agronomic traits.